2013
DOI: 10.2480/agrmet.69.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light intensity and amount of supplemental LED lighting on photosynthesis and fruit growth of tomato plants under artificial conditions

Abstract: We assessed the effects of light intensity (photosynthetic photon flux [PPF in µmol·m -2 ·s -1 ]) and number of irradiated leaves on photosynthesis and the fruit growth of individual tomato plants to develop supplemental LED lighting techniques for greenhouse tomato production. In Experiment (Exp.) 1, three PPF levels (P200, P500, and P1000) were applied to a post-anthesis tomato plant for three weeks, each plant pruned to have one leaf and one truss with three flowers. The fruit set and leaf and fruit dry-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Previous studies in this area are few (Fierro et al, 1994;Hikosaka et al, 2013;Nilsen et al, 1983). Here we investigate the effects of CO 2 enrichment and supplementary light on photosynthesis, growth, yield, and quality of tomatoes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in this area are few (Fierro et al, 1994;Hikosaka et al, 2013;Nilsen et al, 1983). Here we investigate the effects of CO 2 enrichment and supplementary light on photosynthesis, growth, yield, and quality of tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has focused largely on the effects of individual factors of supplementary light or supplementary CO 2 on plant growth, yield, and quality (Hikosaka et al, 2013;Mamatha et al, 2014;Yelle et al, 1990;Zou et al, 2016). Urban et al (2014) reported that the enhancement of photosynthesis under CO 2 enrichment is strongly affected by light intensity.…”
mentioning
confidence: 99%
“…Moreover, LED light sources within a narrow band of the spectrum (light quality) can match to preferred wavelengths of the plant photoreceptors to regulate plant development and physiology (Singh et al ). Supplemental red plus green LED light for strawberries increased the leaf dry mass, fruit yield and soluble solids by 2.0, 2.4 and 1.1 times, respectively, compared with that of the control (Hidaka et al , Hikosaka et al ). Red or blue LED light‐supplementation can affect abscisic acid metabolism and anthocyanin synthesis in grape skin by regulating the expression of secondary metabolism‐related genes (Kondo et al ).…”
Section: Introductionmentioning
confidence: 92%
“…Generally, plants can be classified as either annual, biennial, or perennial. The Pn in tomato plants, which is an annual plant, ranges from 15 to 20 mol CO2 m 2 s 1 at light saturation point with or without SL (Hikosaka et al, 2013). In contrast, the Pn in perennial woody plants is about 4 to 8 mol CO2 m 2 s 1 at light saturation point (Reich et al, 1998).…”
Section: Resultsmentioning
confidence: 99%